“Moderasi beragama di era digital: analisis pesan dakwah habib ja’far dalam login podcast” - Hendra, M.Hendra (Maliki Interdisciplinary Journal, 2025)
The phenomenon of religious intolerance remains a serious challenge in Indonesia, marked by cases of rejection of the construction of houses of worship, persecution of minority groups, and the rise of hate speech in public spaces. Religious moderation is one solution offered to maintain social harmony by emphasizing national commitment, tolerance, anti-violence, and respect for local culture. In the digital era, preaching and education about moderation are not only carried out through direct interactions, but also through social media. This study aims to analyze the preaching messages of Habib Husein Ja'far al-Hadar in the Login Podcast, broadcast on Deddy Corbuzier's YouTube channel with Onadio Leonardo. Using a qualitative approach and content analysis, this study identified messages of moderation presented in a relaxed, humorous, yet substantial style. The analysis results show that the Login Podcast consistently conveys the values ​​of tolerance, respect for diversity, and calls to avoid violence. Furthermore, the interfaith discussions presented in several episodes provide a space for inclusive dialogue that encourages mutual respect. The findings of this study confirm that digital media can be an effective means of instilling the value of moderation, especially among the younger generation familiar with popular culture. Therefore, entertainment-based Islamic preaching content like the Login Podcast can be an alternative public education tool capable of addressing the challenges of intolerance in the digital age.